FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PRAKTIK PEMANFAATAN PELAYANAN KESEHATAN PEDULI REMAJA (PKPR) OLEH REMAJADI WILAYAH KERJA PUSKESMAS BANDARHARJO KOTA SEMARANG - Alifia Nur Laili; Emmy Riyanti; Syamsulhuda BM (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
PKPR is a health service model that serves all adolescents in the form of counseling and various things related to adolescent health. The adolescent health coverage program at Bandarharjo Health Center is quite low at 73.23%. Bandarharjo Health Center has thorough cases in Semarang City, which are 108 cases of KTD (Unwanted Pregnancy) and 4 cases of STI (Sexually Transmitted Infections). This study is to find out what factors are related to the practice of using PKPR by adolescents in the Bandarharjo Health Center work area. This research is a quantitative research using cross sectional. The sample chosen using the Simple Random Sampling technique is 95 adolescents about 15-19 years. Data collection was conducted through interviews using a questionnaire. Data analysis was carried out in univariate and bivariate ways. From the results of the study found that 51 adolescents (53.7%) had used PKPR services. The majority of respondents who there were accompanied by late age were 17-19 years (67.4%), male (51.6%), had the last education of junior high school (52.6%). The results of the bivariate analysis showed that there was a relationship between knowledge (p = 0.024), attitude (p = 0.007), family (p = 0.024), and information exposure (p = 0.004) with the practice of using PKPR by adolescents. While the income variable (p = 0.778), gender (p = 0.591), last education (p = 0.075), friends (p = 0.525), health (p = 0.736), access to health services (p = 0.238) and the counseling room (p = 0.951) has nothing to do with the practice of using PKPR by adolescents.